Evaluating Suicide Risk Using the Reasons for Dying-Reasons for Living (RFD-RFL) Index in a Military Psychiatric Inpatient Setting. (January 2021) - Fox, Amber M.; LaCroix, Jessica M.; Bond, Allison E.; Perera, Kanchana U.; Luk, Jeremy W.; Goldston, David; Weaver, Jennifer; Soumoff, Alyssa; Ghahramanlou-Holloway, Marjan
Highlights: We describe reasons for living and dying among military service members hospitalized for a recent suicide-related crisis The most reported and top ranked reason for dying is general self-descriptors The most reported and top ranked reason for living is family Reporting more reasons for dying relative to reasons for living is associated with suicide risk indicators Abstract: The present study aimed to explore reasons for dying (RFD) and reasons for living (RFL) among suicidal inpatients, conceptualize the RFD-RFL index, and examine whether suicide risk indicators were associated with the RFD-RFL index scores. Participants were military personnel ( N = 167) psychiatrically hospitalized following a suicide-related crisis who provided baseline data as part of a randomized controlled trial. Family was the most commonly reported RFL (39.7%) and was the top ranked RFL for 65.9% of participants. The most frequently endorsed RFD categories included general descriptors of self (26.9%), general statements about escape (19.7%), and others/relationships (19.1%). Greater RFD-RFL index scores were associated with a greater wish to die relative to wish to live, greater hopelessness, and with a history of lifetime multiple suicide attempts. Endorsing more RFD relative to RFL may indicate heightened suicide risk. Results of this study identify the characteristics of RFD and RFL among a high-risk, military sample, and provide preliminary support for the clinical utility of evaluating the quantities of RFD and RFL. Clinicians are encouraged to explore RFD and RFL when working with suicidal patients. Future research may explore military-specific RFD and evaluate the validity of the proposed RFD-RFL index.